2004
DOI: 10.1016/j.cardiores.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analyses of eight NKX2.5 homeodomain missense mutations causing atrioventricular block and cardiac anomalies

Abstract: Each mutant protein had a unique spectrum of observed properties, but our data show that while dominant negative properties could be demonstrated in vitro, the best correlation with clinical phenotypes resulted from the markedly reduced DNA binding shared by all eight homeodomain mutations. This suggests that the principle determinant of the two most common phenotypes associated with homeodomain missense mutations is the total dose of NKX2.5 capable of binding to DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 41 publications
6
86
0
Order By: Relevance
“…Our results are supported by the finding of other NKX2-5 mutations predisposing to congenital CHD by impairing or reducing cardiac transcription factor NKX2-5 (Kasahara et al, 2000;Kasahara and Benson, 2004). To date, more than 40 mutations in NKX2-5 have been described, of which more than 30 mutations have been observed in patients with atrial septal defect, showing that although NKX2-5 mutations are involved in a long list of cardiac malformations, the most frequent phenotype resulted is atrial septal defect (Stallmeyer et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Our results are supported by the finding of other NKX2-5 mutations predisposing to congenital CHD by impairing or reducing cardiac transcription factor NKX2-5 (Kasahara et al, 2000;Kasahara and Benson, 2004). To date, more than 40 mutations in NKX2-5 have been described, of which more than 30 mutations have been observed in patients with atrial septal defect, showing that although NKX2-5 mutations are involved in a long list of cardiac malformations, the most frequent phenotype resulted is atrial septal defect (Stallmeyer et al, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…The identification that GATA4 mutations associated with CHD have hypomorphic transactivation ability not always explained by DNA binding deficits is consistent with the dosage sensitivity of GATA4. These findings are different from those reported for NKX2-5 mutations which usually exhibit decreased transactivation ability and associated reduced DNA binding affinity [Kasahara and Benson, 2004]. In summary, the results of in vitro biochemical studies are consistent with reports of human patients who have similar types of CHD and harbor deletions of chromosome 8p that lead to haploinsufficiency of GATA4 [Pehlivan et al, 1999].…”
Section: Discussionsupporting
confidence: 68%
“…Subsequently, other investigators have reported additional GATA4 mutations, S52F, E216D and E358del, in individuals with non-syndromic CHD [Okubo et al, 2004;Hirayama-Yamada et al, 2005;Sarkozy et al, 2005;Nemer et al, 2006]. We hypothesize that mutations in GATA4 are present in diverse types of non-syndromic CHD similar to NKX2.5, and that these mutations might result in alterations of Gata4 function in biochemical assays thereby accounting for genotype-phenotype differences [Benson et al, 1999;Kasahara et al, 2000;Goldmuntz et al, 2001;Kasahara and Benson, 2004]. To determine the frequency of GATA4 mutations in patients with non-syndromic CHD, we studied 157 individuals with sporadic and familial cases of CHD and tested novel and previously unstudied GATA4 mutations in biochemical assays to identify in vitro functional deficits.…”
Section: Introductionmentioning
confidence: 73%
“…Although Thr 41 is not involved in direct hydrogen bonding with the NKX3.1 DNA recognition sequence, it is likely to affect helix III structure and both DNA and protein interactions. The homologous Thr 41 in the human tinman homologue NKX2.5 has been mutated to methionine in a family with hereditary atrial septal defect and atrioventricular block (49). The NKX2.5 (T178M), homeodomain T41M, mutation causes marked reduction in DNA-binding affinity of NKX2.5 but does not affect complex formation either with wild-type NKX2.5 or with GATA4.…”
Section: Discussionmentioning
confidence: 99%